The Effect of Intellectual Capital on Innovative Performance with the Mediating Role of Qazvin Health Staff's Empowerment: A Path Analysis - Omid Khosravizade; Bahman Ahadinezhad; Bibi Sara Sheikh (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Nowadays, since many health care organizations are facing a crisis of declining productivity and labor force stagnation, productivity can be improved through identifying and strengthening the components affecting the labor force productivity and performance. Thus, the present study was aimed at determining the effect of intellectual capital on innovative performance with the mediating role of health staff's empowerment in Qazvin University of Medical Sciences. Methods: This is a descriptive-analytical cross-sectional study carried out in 2021. Three hundred and four staff of the Health Department and Health Networks participated in the research by the available sampling method. The Bontis questionnaire was employed for measuring the intellectual capital, the Spritzer questionnaire for measuring staff's empowerment, and the Huang and Li questionnaire for measuring innovative performance. Moreover, for preliminary data analysis, SPSS25 Software was used as well as AMOS software for structural equation modeling at a significance level of 0.050 %. Results: The results of the path coefficient among the model variables on each path, corresponding to the research hypotheses, are positive, revealing a positive relationship among the research variables. The path coefficient of the direct relationship between intellectual capital and innovative performance was equal to 0.767 (P-value < 0.001). Moreover, the relationship between intellectual capital and empowerment was equal to 0.306, and between empowerment and innovative performance was equal to 0.153, both of which were significant (p < 0.001). Furthermore, indices of fit including NFI = 0.652, RMSEA = 0.064, GFI = 0.710, and CFI = 0.769 exhibited a relatively good fit of the final model. Conclusion: Given the direct relationship between model variables, the University of Medical Sciences' managers and health officials should provide the bed for improving the capacity of human resources and innovative performance through developing intellectual capital besides creating a platform to play an effective role in the organization. Accordingly, effective and innovative performance based on responding to the human resources' changing needs in all sectors may be imagined.